Semen characteristics in HIV-1 positive men and the effect of semen washing. Issue 4 (August 1997) - Lasheeb, A S; King, J; Ball, J K; Curran, R; Barratt, C L; Afnan, M; Pillay, D
Abstract : We have undertaken an analysis of semen from HIV infected men with regard to sperm counts and motility, non-spermatozoal cells, and viral nucleic acid. Regression analysis showed that sperm concentration and motility were positively associated with blood CD4 cell count. By contrast, non-spermatozoal cell concentration (round cells) was inversely related to CD4 count. Extracellular HIV RNA was detected in the majority of semen samples and proviral DNA in a minority. Percoll gradient washing of 12 semen samples yielded six samples containing adequate sperm concentration for analysis. This washing procedure reduced prewash extracellular RNA to below detectable limits in all cases; proviral DNA present in two of the six prewash samples was also reduced to below detectable limits after washing. We conclude that semen washing before artificial insemination may reduce the risk of HIV transmission from an infected man to an uninfected woman. However, further evidence from prospective analyses of such an approach is required.